Highlight of Immune Pathogenic Response and Hematopathologic Effect in SARS-CoV, MERS-CoV, and SARS-Cov-2 Infection - Liang, Yanwen; Wang, Mong-Lien; Chien, Chian-Shiu; Yarmishyn, Aliaksandr A.; Yang, Yi-Ping; Lai, Wei-Yi; Luo, Yung-Hung; Lin, Yi-Tsung; Chen, Yann-Jang; Chang, Pei-Ching; Chiou, Shih-Hwa (Frontiers in Immunology, 2020)
A sudden outbreak of COVID-19 caused by a novel coronavirus, SARS-CoV-2, in Wuhan, China in December 2019 quickly grew into a global pandemic, putting at risk not only the global healthcare system, but also the world economy. As the disease continues to spread rapidly, the development of prophylactic and therapeutic approaches is urgently required. Although some progress has been made in understanding the viral structure and invasion mechanism of coronaviruses that may cause severe cases of the syndrome, due to the limited understanding of the immune effects caused by SARS-CoV-2, it is difficult for us to prevent patients from developing acute respiratory distress syndrome (ARDS) and pulmonary fibrosis (PF), the major complications of coronavirus infection. Therefore, any potential treatments should focus not only on direct killing of coronaviruses and prevention strategies by vaccine development, but also on keeping in check the acute immune/inflammatory responses, resulting in ARDS and PF. In addition, potential treatments currently under clinical trials focusing on killing coronaviruses or on developing vaccines preventing coronavirus infection largely ignore the host immune response. However, taking care of SARS-CoV-2 infected patients with ARDS and PF is considered to be the major difficulty. Therefore, further understanding of the host immune response to SARS-CoV-2 is extremely important for clinical resolution and saving medication cost. In addition to a breif overview of the structure, infection mechanism, and possible therapeutic approaches, we summarized and compared the hematopathologic effect and immune responses to SARS-CoV, MERS-CoV, and SARS-CoV-2. We also discussed the indirect immune response caused by SARS and direct infection, replication, and destroying of immune cells by MERS-CoV. The molecular mechanisms of SARS-CoV and MERS-CoV infection-induced lymphopenia or cytokine storm may provide some hint toward fight against SARS-CoV-2, the novel coronavirus. This may provide guidance over using immune therapy as a combined treatment to prevent patients developing severe respiratory syndrome and largely reduce complications.